EIB Working Papers 2020/04 - Making a difference Assessing the impact of the EIB's funding to SMEs (Volume 2020/4) - Gereben, Áron (European Investment Bank, 2020)
This paper investigates the impact of intermediated funding provided by the EIB on the performance of SMEs in the EU between 2008 and 2014. Using statistical analysis of firm-level data, it finds that EIB lending had a positive effect on employment, firm size, investment and innovation capacity, and also increased firms' leverage. The impact of EIB funding was higher in the countries of Central and Eastern Europe and also in Southern Europe, while somewhat smaller, yet still significant, in West and North Europe.